How Chinese Money is Transforming Africa: It's Not What You Think - Jyhjong Hwang; Deborah Brautigam; Janet Eom (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2016)
When, why, and how are Chinese banks really financing African development? This policy brief presents CARI researchers' analysis of Chinese loans in Africa, drawing from data collected and cleaned by CARI since 2007. Between 2000 and 2014, the Chinese government, banks and contractors extended US 86.3 billion worth of loans to African governments and state-owned enterprises (SOEs). Angola received the most Chinese loans, totally 21.2 billion over the past 15 years, followed by Ethiopia (12.3 billion) and Sudan (5.6 billion). Transportation, energy, and mining are the three largest sectors financed by Chinese loans in Africa.
Keywords: 330